Estudo eletromiogr??fico pr?? e p??s estimula????o transcraniana por corrente cont??nua associada ao treino funcional de membro superior para crian??as com paralisia cerebral hemipar??ticas esp??sticas: ensaio cl??nico controlado aleatorizado e duplo cego - Santos, Cibele Almeida (2015)
Objective: To analyze the effect of transcranial direct-current stimulation of the primary motor cortex associated with functional training of paretic upper limb of children with cerebral palsy type spastic hemiparesis, levels I to III of MACS on the synergistic muscle activity of the biceps and triceps brachial by electromyography. Materials and Methods: Study I: A search was conducted in five Medline, PEDro, Lilacs, SciELO and PubMed, according to the following criteria: randomized controlled trial; outcome: functional evaluation of the upper limbs of individuals with cerebral palsy; published between 2006 and 2014. Methodological quality was assessed according to the PEDro scale. Study II: The sample comprised 21 children with hemiparetic spastic cerebral palsy were randomly allocated into two groups: experimental - 11 children (the functional training of the paretic upper limb with transcranial stimulation anode) and control - 10 children (functional training of the upper limb paretic with transcranial stimulation Sham), between 6 and 15 years old. The evaluation was performed by electromyography of the biceps and triceps brachial bilaterally. 10 training sessions were conducted for two consecutive weeks, five sessions per week (20 minutes each). Results: Study I: Six controlled trials addressing functional evaluation of the upper limbs of individuals with cerebral palsy were found. Presented methodological quality of six points or more on the PEDro scale. Study II: The experimental group showed a significant result (p <0.05) in evaluation on the paralyzed side to Biceps Brachial (in extension and flexion) between PRE ratings, immediately AFTER 1 Session, AFTER 10 sessions and 1 month, but for Triceps Brachial was only found significant result during extension between assessments and PRE AFTER 1 month. Conclusion: Although there are different scales of assessment, there is no consensus on how best to use to evaluate the function of the upper limbs in cerebral palsy. And based on the results we suggest that the tDCS associated with functional training of the upper limbs has an effect on muscle activity.